Multiparameter diffusion‐weighted imaging for characterizing pathological patterns in lupus nephritis patients: A preliminary study. Issue 4 (18th January 2019) - Zhang, Shan; Lin, Yanwei; Ge, Xin; Liu, Guiqin; Zhang, Jianjian; Xu, Shuaishuai; Wu, Guangyu; Chen, Sheng; Xu, Jianrong; Suo, Shiteng
Abstract : Background: Microstructural changes of lupus nephritis (LN) kidney such as inflammatory cell infiltration or fibrosis could influence water molecular movement or diffusion, which indicates that diffusion‐weighted imaging (DWI) may become a valuable tool in evaluation of this disease. Purpose: To explore whether multiparameter diffusion‐weighted imaging (mDWI) could contribute to characterize pathological patterns in LN patients. Study Type: Retrospective. Population: Twenty‐two patients with LN. Field Strength/Sequence: Multi‐b value DWI was performed with a 3.0 T scanner. Assessment: Apparent diffusion coefficient (ADC)m, perfusion‐related diffusion coefficient (Df ), molecular diffusion coefficient (Ds ), perfusion fraction ( f ), ADCs, α, ADCk, and mean kurtosis (MK) were calculated by monoexponential, biexponential, stretched‐exponential, and kurtosis models fits, respectively. Statistical Tests: Independent sample t ‐test, Pearson analysis and receiver operating characteristic (ROC). Results: In the whole group, the activity index (AI) correlated significantly with alpha values in the medulla (rho = –0.54, P = 0.03). The chronicity index (CI) correlated significantly with Ds values in the medulla (rho = –0.61, P = 0.02). No significant association was found between any other diffusion parameter and histologic grade with all P > 0.05. For differentiating proliferative LN (Class III or IV) from Class V, the area under the ROC curve (AUC) of alpha in the medulla was 0.833 ( P = 0.023). Data Conclusion: mDWI might be used for the characterization of pathological patterns in LN patients. Level of Evidence: 3 Technical Efficacy Stage: 2 J. Magn. Reson. Imaging 2019;50:1075–1084.